ANALISIS PENGARUH INVESTASI, INDEKS PEMBANGUNAN MANUSIA DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI (Studi Pada Sumatera Barat Tahun 2010-2019) - Syofria Meidona; Virell Prastama; Elsa Fitri Amran (UIN Mahmud Yunus Batusangkar, 2021)
This study aims to determine how to analyze the effect of investment, human development index and labor on the economic growth of West Sumatra in the 2010-2019 period. The data used in this study is secondary data, namely panel data consisting of time series data over a period of ten years, namely 2010-2019. The method used for sampling this research using saturated sampling. This study uses the SPSS program version 23. Based on the hypothesis testing carried out using multiple linear regression analysis with the results Y = 20.139 +0.001 X1 - 0.208 X2 - 0.017 X3 at a significance level of 0.05 on the three variables, with an investment value of tcount 0.774 <ttable1,943, sig value 0.468> 0.05 indicates a positive direction, HDI tcount -3.360> t table 1.943, sig value 0.015 <0.05 indicates negative direction, and Labor tcount 0.774 <t table 1.943, Sig value 0.58> 0.05 indicates Negative direction, the results of this study prove that partially the human development index has an effect on economic growth, while the investment and labor variables have no effect on economic growth. The results of simultaneous research on investment, human development index, and labor have a significant effect on economic growth with tcount 5,137> ttable 4,76, sig value 0.043 <0.05.